2016
DOI: 10.12660/rbfin.v14n1.2016.53448
|View full text |Cite
|
Sign up to set email alerts
|

Os Fatores Determinantes do Pagamento de Dividendos: o Efeito do Obrigatório Mínimo Legal e Contratual nas Empresas Brasileiras

Abstract: This study seeks to identify the effects of the mandatory dividend in determinants of companies listed on the BM&FBovespa to pay dividends, demonstrating that the methodology proposed is a step forward in the pursuit of these determinants, mirroring the reality of actual willingness to pay. To accomplish this was used a tobit model with instrumental variables, separating the sample into t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
1
21

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(37 citation statements)
references
References 17 publications
1
14
1
21
Order By: Relevance
“…In a recent paper, Vancin and Procianoy (2016) find that the legislation has an important role in the determinants of dividend policy. They find that there is strong empirical evidence that companies paying dividends above the legal mandatory level present different determinants from those that only pay the minimum level.…”
Section: Previous Empirical Evidence On Dividend Policy In Brazilmentioning
confidence: 99%
“…In a recent paper, Vancin and Procianoy (2016) find that the legislation has an important role in the determinants of dividend policy. They find that there is strong empirical evidence that companies paying dividends above the legal mandatory level present different determinants from those that only pay the minimum level.…”
Section: Previous Empirical Evidence On Dividend Policy In Brazilmentioning
confidence: 99%
“…The minimum dividend constraint imposed by law may be binding for some firms, due to their financial realities and investment opportunities, and thus we can expect that their investment and financial decisions may change relative to what would be in the absence of such constraint. Vancin and Procianoy (2016) state that there is a basic difference between the companies that pay the minimum mandatory dividend and those that pay above this amount. It is observed that the former are compelled by law to make some payment of dividends.…”
Section: Methodsmentioning
confidence: 99%
“…According to Vancin and Procianoy (2016), Brazilian reality regarding low availability of long-term resources to finance investment activities is a great incentive for high retention of cash by companies. Therefore, in general, internal financing has great importance for national company's investment policy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…v. 11, n. 1, p. 58 -76, Jan./Jun. 2019, ISSN 2176 é parte do lucro das organizações paga aos investidores como forma de remuneração do seu capital investido (Kania, & Bacon, 2005;Vancin, & Procianoy, 2016).…”
Section: Política De Dividendosunclassified